2018
DOI: 10.1007/s10637-018-0647-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of apratoxin S10 (Apra S10) as an anti-pancreatic cancer agent and its preliminary evaluation in an orthotopic patient-derived xenograft (PDX) model

Abstract: Despite the significant progress in the field of cancer therapeutics, the incidence of pancreatic cancer (PC) has continuously increased. One possible mechanism for this increasing burden is impaired drug delivery and drug resistance resulting from a unique tumor microenvironment and genetic mutations. Apratoxins are potent anticancer agents and cotranslational translocation inhibitors with potential therapeutic applications to treat cancers with active secretory pathways. Here, we developed apratoxin S10 (Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Apratoxins were previously reported to exert its function by inhibiting protein co-translational translocation at the level of Sec61 translocon, leading to downregulation of various receptor tyrosine kinases and growth factors. 13,14,[16][17][18]36 Consistent with these observations [20], receptor tyrosine kinase VEGFR2 and VEGFR3 expressions were significantly inhibited in Apratoxin S4-treated HRECs. Similarly, receptor tyrosine kinase PDGFR-b level in HRPCs was also suppressed by Apratoxin S4.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Apratoxins were previously reported to exert its function by inhibiting protein co-translational translocation at the level of Sec61 translocon, leading to downregulation of various receptor tyrosine kinases and growth factors. 13,14,[16][17][18]36 Consistent with these observations [20], receptor tyrosine kinase VEGFR2 and VEGFR3 expressions were significantly inhibited in Apratoxin S4-treated HRECs. Similarly, receptor tyrosine kinase PDGFR-b level in HRPCs was also suppressed by Apratoxin S4.…”
Section: Discussionsupporting
confidence: 73%
“…Natural and synthetic Apratoxins are potent antitumor and antiangiogenic macrocyclic depsipeptides derived from marine cyanobacteria. [16][17][18]35,36 It was reported that Apratoxins exert their function through inhibiting co-translational translocation of secreted or membrane bound proteins, 13 which may offer an alternative way to control the activation of angiogenic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Sandra Ramos-Inza 1,2 , Carlos Aydillo 1,2 , Carmen Sanmartín 1,2 and Daniel Plano 1,2 * 1 Faculty of Pharmacy and Nutrition, Department of Pharmaceutical Technology and Chemistry, University of Navarra, Pamplona, Spain 2 Instituto de Investigación Sanitaria de Navarra (IdiSNA), Pamplona, Spain *Address all correspondence to: dplano@alumni.unav.es (R)-C 30 thiazoline and the addition of a methyl group at C 34 , shows potent in vitro angiogenesis and vascularized tumor cell growth inhibition [93]. It showed antipancreatic cancer activity, including in orthotopic pancreatic patient-derived xenograft mouse model [94]. Other derivatizations consisting of thiazoline substitution by piperidinecarboxylic acid moiety have been developed [95].…”
Section: Author Detailsmentioning
confidence: 99%
“…The PDOX models of PDAC were established as described previously. 33 35 Once acquired from the specimen, the tumor was cut into fragments of approximately 3mm 3 to transplant subcutaneously into NOD/SCID mice as the first generation. Then, the nude mice were implanted with the patient tumor growing in NOD/SCID mice as the second generation to establish the models.…”
Section: Methodsmentioning
confidence: 99%